7 Recommendations to Foster Internationalization in Education (Journal of Parents and Teachers, 2025)
A professor from the United States shares some advice based on her experience as a foreigner having to learn another language and culture to be able to teach this better to her students.
Keywords: internationalization; future teachers; intercultural experiences; language learning